Effects of air pollution on the Rivne population morbidity rate - Лико, Д. В.; Каськів, М. В. (Man and Environment. Issues of Neoecology, 2014)
There are the problem of the impact of air pollution on morbidity in different age groups of the population. Installed polynomial dependence between the values of toxic emissions into the atmosphere and morbidity of the population. Prospects for further research should be considered studying the chemistry of air pollutants in some areas rivne , especially in the areas of industrial and streets with heavy traffic vehicles.